Angular and polarization trails from effective interactions of Majorana neutrinos at the LHeC - Lucía Duarte; Gabriel Zapata; Oscar A. Sampayo (European Physical Journal C: Particles and Fields, 2018)
Abstract We study the possibility of the LHeC facility to disentangle different new physics contributions to the production of heavy sterile Majorana neutrinos in the lepton number violating channel $$e^{-}p→ l_{j}^{+} + 3 jets$$ e-p→lj++3jets ($$l_j\equiv e ,μ $$ lj≡e,μ ). This is done investigating the angular and polarization trails of effective operators with distinct Dirac–Lorentz structure contributing to the Majorana neutrino production, which parameterize new physics from a higher energy scale. We study an asymmetry in the angular distribution of the final anti-lepton and the initial electron polarization effect on the number of signal events produced by the vectorial and scalar effective interactions, finding both analyses could well separate their contributions.